2006
DOI: 10.1248/cpb.54.152
|View full text |Cite
|
Sign up to set email alerts
|

Highly Oxygenated Guaianolides and Eudesman-12-oic Acids from Balsamorhiza sagittata and Balsamorhiza macrophylla

Abstract: Investigation of lipophilic exudates from the aerial parts of Balsamorhiza sagittata and B. macrophylla afforded three new highly oxygenated guaianolides (1-3), in addition to known guaianolides, germacranolide and eudesmane acids. Their chemical structures were elucidated by spectroscopic methods and the data for the compounds are reported in Tables 1 and 2 and in Experimental.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…The structures 389 or 390 were proposed. The exudates of the aerial parts of Balsamorhiza sagittata and Balsamorhiza macrophilla 354 contain the new guaiane derivative 391. A study of a methanolic extract from the fruits of Torilis japonica 355 afforded the cytotoxic sesquiterpenes torilin 392, 1ahydroxy-torilin 393 and the new metabolite 1b-hydroxy-torilin 394.…”
Section: Guaiane Pseudoguaiane Xanthane and Patchoulanementioning
confidence: 99%
“…The structures 389 or 390 were proposed. The exudates of the aerial parts of Balsamorhiza sagittata and Balsamorhiza macrophilla 354 contain the new guaiane derivative 391. A study of a methanolic extract from the fruits of Torilis japonica 355 afforded the cytotoxic sesquiterpenes torilin 392, 1ahydroxy-torilin 393 and the new metabolite 1b-hydroxy-torilin 394.…”
Section: Guaiane Pseudoguaiane Xanthane and Patchoulanementioning
confidence: 99%
“…This ever-growing class of important secondary metabolites possesses a wide range of biological properties, which include plant growth inhibition, insect antifeedant, antibacterial, antifungal, and antitumor activities. Representative eudesmanes include antibacterial agents (+)-carissone ( 1 ) and (+)-3-oxocostusic acid ( 2 ), as well as P/Q-type calcium channel blocker (−)-α-eudesmol ( 3 ) (Figure ). These examples typify common structural motifs within this class of sesquiterpenoids, including the C(10) all-carbon quaternary stereocenter and stereogenic C(7) substituent.…”
mentioning
confidence: 99%
“…Compound 1 was purified in a white amorphous powder. The 1 H NMR spectrum of 1 observed characteristic signals of 5 olefinic protons at δH 6.29 Measured at a) CDCl3, b) 125 MHz, c) 500 MHz, #) Reported by Mohamed et al, [13] $) Reported by Quijano et al, [14] NR) Not reported. Signals were assigned based on HSQC and HMBC experiments.…”
Section: Resultsmentioning
confidence: 99%
“…9β-Acetoxy-3-epi-nobilium (1): H NMR (500 MHz, CD3OD) δH in ppm: 7.76 (1H, dd, J = 2.0 and 8.0 Hz, H-6), 7.53 (1H, dt, J = 2.0 and 8.0 Hz, H-4), 7.40 (1H, dd, J = 2.0 and 8.0 Hz, H-3), 7.13 (1H, dt, J = 2.0 and 8.0 Hz, H-5), 3.90 (3H,s, 7-OCH3); sugar moiety: 4.90 (1H, d, J = 7.5, Glc H-1), 3.91 (1H, dd, J = 2.0 and 12.0, Glc Ha-6), 3.74 (1H, dd, J = 5.5 and 12.0, Glc Hb-6), 3.55 (1H, t, J = 9.0, Glc H-4), 3.54 (1H, t, J = 9.0, Glc H-3), 3.48 (1H, m, Glc H-5), 3.44 (1H, dd, J = 7.5 and 9.0, Glc H-2); 13 C NMR (125 MHz, CD3OD) δC in ppm: 168.6 (C-7), 158.7 (C-2), 135.1 (C-4), 132.0 (C-6), 123.7 (C-5), 122.4 (C-1), 119.0 (C-3), 52.8 (7-OCH3); sugar moiety: 104.1 (Glc C-1), 78.5 (Glc C-5), 77.5 (Glc C-3), 75.1 (Glc C-2), 71.3 (Glc C-4), 62.6 (Glc C-6); HR-ESI-MS: found m/z 349.0686 [M+ 35 Cl] -, calcd. for [C14H18O8 35 Cl] -: 349.0696, Δ = -2.8 ppm, found m/z 351.0666 [M+ 37 Cl] -, calcd.…”
Section: Extraction and Isolationmentioning
confidence: 99%
See 1 more Smart Citation